Optimal GHG Emission Abatement and Aggregate Economic Damages of Global Warming - Kanellos, Fotis D.; Grigoroudis, Evangelos; Hope, Chris; Kouikoglou, Vassilis S.; Phillis, Yannis A. (IEEE systems journal, 2017)
Man-made global warming poses serious threats to the environment and society. Proper abatement policies for greenhouse gas (GHG) emissions are urgently needed to ameliorate the effects of global warming. In this paper, we introduce a version of the Policy Analysis of the Greenhouse Effect (PAGE) model that is faster by two orders of magnitude than previous versions. PAGE is then used in conjunction with a genetic algorithm to devise optimal GHG emission abatement policies. Such policies are chosen so that an overall cost is minimized subject to certain constraints imposed on the policies. The results show the urgency of the problem. It turns out that an additional warming of 3 °C to 4 °C, as compared to the year 1900, imposes enormous stresses on the global economy. This paper highlights the urgency of climate action in the form of drastic emission cuts.